Ya 'Ayb al-Shoum: Scenes of Auto/Bio/Graphy and Shame in Nadine Naous's Home Sweet Home. Issue 2 (3rd April 2018) - Nikro, Norman Saadi
ABSTRACT: Many filmmakers and people working in film projects in Lebanon over the last two decades are interested in gathering and telling the stories of their parents' generation, towards understanding and acting on their present social, cultural, and political circumstances. Where literary autobiographical fiction and memoir has tended to be produced by an older generation that lived through the violence of the civil war years (1975–1990), documentary film is an expanding auto/biographical practice of cultural production by a younger, post-civil war generation. While such films consist of strands of biography, soliciting personal stories of their parents' generation, they also contain impulses of autobiography, often foregrounding the filmmaker's own story in relation to their interest in tracking the stories they collect. In this essay I explore auto/bio/graphical impulses in the documentary film Home Sweet Home (2014), by Nadine Naous. By situating Naous's film as a site of address and response, I consider to what extent the relational impulses of her father's story and her's implicate embodiments of shame as gendered modalities of decorous conduct.